Estrutura e competitividade do setor têxtil cearense e brasileiro no período de 2000 a 2011 - Souza, Ana Cristina Lima Maia (2014)
Brazilian textile industry felt the effects caused by the changes occurred in the last three decades, like the insertion of new inputs and consequently new products, as well as the commercial opening and Real Plan. In this way Brazil’s textile industry has been losing share in the economy on the country and also in the world market. This performance has also been observed in the textile industry of Ceará, where the conjunctural researches indicated a loss above the national average. In this context, this study aims to investigate the competitiveness of textile industry of Brazil and Ceará. It was used the Porter´s five forces theory, with the construction of indexes compared with the main states comprising Brazilian textile sector to evaluate the competitiveness of the textile sector of Ceará. Profits were measured through statistical methodology in a panel data, to analyse the competitiveness of Brazilian textile industry. In the development of this work, it was used data from the Annual Industrial Survey conducted by IBGE and Aliceweb’s data. The results indicated that the textile industry of Ceará showed elevated productivity per worker and one of the lowest production costs. But the industry in this state showed fragility in the supply of inputs by foreign market and little product diversity. As for Brazilian textile industry, we realized that the profits are positively related to the cost of raw material and wages and inverse expenses with social charges. In the macroeconomic extent, the results showed that the foreign market has less influence on the textile sector than the industrial costs.